The European Constitution Project from the Perspective of Constitutional Political Economy - Lars P. Feld (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Three topics of a European constitution are discussed. First, basic arguments from constitutional political economy that aim at restricting representatives' potential misuse of powers in a European Union with extended competencies are summarized. Since a European demos does not yet exist, an extension of competencies of the Euro¬pean Parliament is not sufficient in order to legitimate political decisions at the EU le¬vel. The introduction of elements of direct democracy in the European constitution would shape the creation of such a demos and lead to a stronger control of the European legislature and executive. Second, the introduction of direct democracy in the European constitution is proposed in order to reduce the European democratic deficit. Third, the creation of a European federation requires a more transparent assignment of competen¬cies and rules to resolve conflicts between different centers of power. A European fede¬ration should be organized according to the principles of competitive federalism.
Keywords: D78; 330; European Constitutional Convention; Bill of Rights; Separation of Powers; Competitive Federalism; Referendums; European demos